2012
DOI: 10.1093/pcp/pcs130
|View full text |Cite
|
Sign up to set email alerts
|

Florigenic and Antiflorigenic Signaling in Plants

Abstract: The evidence that FLOWERING LOCUS T (FT) protein, and its paralog TWIN SISTER OF FT, act as the long-distance floral stimulus, or at least that they are part of it in diverse plant species, has attracted much attention in recent years. Studies to understand the physiological and molecular apparatuses that integrate spatial and temporal signals to regulate developmental transitions in plants have occupied countless scientists and have resulted in an unmanageably large amount of research data. Analysis of these d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
85
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 180 publications
(227 reference statements)
1
85
0
Order By: Relevance
“…It has also been suggested that an increase in the source to sink sugar flow through the phloem may help transport florigenic substances, such as FT, that trigger the floral response in the meristem (Corbesier et al, 1998). Moreover, the activation of phloem-and meristem-specific sugar transporters associated with the flowering process (Matsoukas et al, 2012) strongly suggests this effect. Based on these findings, we propose a mechanism by which CO alteration of GBSS expression may help to liberate large amounts of sugars during the floral transition ( Figure 7).…”
Section: Discussion Transitory Starch Accumulation Depends On Daylengmentioning
confidence: 99%
“…It has also been suggested that an increase in the source to sink sugar flow through the phloem may help transport florigenic substances, such as FT, that trigger the floral response in the meristem (Corbesier et al, 1998). Moreover, the activation of phloem-and meristem-specific sugar transporters associated with the flowering process (Matsoukas et al, 2012) strongly suggests this effect. Based on these findings, we propose a mechanism by which CO alteration of GBSS expression may help to liberate large amounts of sugars during the floral transition ( Figure 7).…”
Section: Discussion Transitory Starch Accumulation Depends On Daylengmentioning
confidence: 99%
“…SPL3 and SPL9 members in the SAM directly promote the activation of floral meristem identity genes Yamaguchi et al, 2009). SPL9-like members have additional functions in leaves, where they activate the transcription of miR172b, which lowers the abundance AP2-like floral repressor transcripts and allows accumulation of FT mRNA (Zhu and Helliwell, 2011;Matsoukas et al, 2012;Wang, 2014).…”
Section: The Mir156-spl-mir172 Module As a Hub For Integration Of Flomentioning
confidence: 99%
“…During the night, CO is rapidly degraded by the proteasome and FT expression is repressed (Valverde et al, 2004). Upon its production at dusk, the FT protein moves from phloem to the SAM, where it interacts with the locally transcribed FLOWERING LOCUS D (FD) transcription factor to activate floral integrators like SOC1 and AGL24 to induce flowering (Amasino, 2010;Matsoukas et al, 2012). Accordingly, genetic studies have placed the age pathway parallel with the photoperiodic pathway (Wang, 2014), both being required to determine the threshold of FT necessary for flowering competence.…”
mentioning
confidence: 99%